Islam dan Pergeseran Pandangan Hidup Orang Tolaki - Idaman Idaman; Rusland Rusland (Al-Ulum, 2012)
Islam has significantly influenced the change and way of life of the people of Tolaki in Kunawe, Southeast Sulawesi. The Tolaki’s way of life can be traced within folklore which stil transmitted from generation to generation. Analysis of the folklore, such as, Langgai Moriana Ndotongano Wonua dan I Sandima, revealed that since Islam came to this region, there has constantly been shifting within society, both in terms of concept and daily life of the Tolaki peoples. It is mentioned, for example, in the Langgai Moriana Ndotongano Wonua, that Islam has changed the belief of Sangia to Allah. Also, Islam influenced almost all traditions of Tolaki, marriage, human relation, environment, social relation and stratification. In other folklore, I sandima, the change also took place in the area from animism to Islam and relation between the Tolaki people and their nature. Since the coming of Islam in ‘Negeri para Sangia’, it is inherently coming into daily lives of Tolaki community.